Pengaruh Pemberian Media Kartu Kuartet Terhadap Pengetahuan Tentang Napza Pada Anak Sekolah Dasar - Rionaldo Yogi Pradesta; Dian Susmarini; Aris Fitriyani; Maisje Marlyn Kuhu (Prodi Keperawatan Purwokerto, 2021)
Background: Drug addiction is one of effect from drug abuse. Knowledge become one of factors that relate to drug abuse. Health education media, especially quartet card game, is well known can increase knowledge. The aim of this study is to seek an effect of quartet card game to knowledge about drug abuse in elementary school’s children.Methods: This study used quasi experiment with control group and posttest design. The sampling technique used total sampling with 80 respondents and respondents were separated into intervention and control group. Wilcoxon test were used as data analysis.The Results: There was significant effect of quartet media with knowledge of drug abuse in elementary school’s children (p=0,000).Conclusion: Quartet card’s game has an effect for knowledge of drug abuse in elementary school’s children.